Case Report: Evolution and targeted therapy of an EGFR-mutant large-cell neuroendocrine carcinoma - Jiang, Li; Yao, Xiaowen; Cai, Xiuyu; Li, Pengfei (Frontiers in Oncology, 2025)
We report the case of a 47-year-old female non-smoker diagnosed with stage IV large-cell neuroendocrine carcinoma (LCNEC) of the lung harboring an EGFR exon 21 L858R mutation. The patient exhibited a sustained response to first-line osimertinib, with a progression-free survival of 20 months, followed by transformation to small-cell lung cancer (SCLC) confirmed via histopathological reassessment. Second-line treatment with etoposide and cisplatin combined with radiotherapy resulted in an additional 7 months of disease control. Subsequent progression was accompanied by features suggestive of adenocarcinoma, supported by elevated carcinoembryonic antigen levels, stable neuron-specific enolase, and circulating tumor DNA profiling. Third-line chemotherapy with paclitaxel, carboplatin, and bevacizumab, followed by maintenance therapy with aumolertinib and anlotinib, extended progression-free survival by 21 months. Overall survival reached 48 months. This case highlights the critical importance of repeated molecular profiling and histologic reevaluation in guiding therapeutic decisions for EGFR-mutant LCNEC undergoing phenotypic evolution.